2001
DOI: 10.1002/dev.1016
|View full text |Cite
|
Sign up to set email alerts
|

Selective breeding for infant vocal response: A role for postnatal maternal effects?

Abstract: N:NIH rats were selectively bred on the basis of high or low rates of ultrasonic vocalization (USV) response to isolation at 10 days of age (Brunelli et al., 1997: Dev Psychobiol 31:255-265). To examine the possibility of postnatal maternal effects in the generational transmission of divergent traits, pups were cross-fostered shortly after birth between dams of the two lines (Low- and High-USV). Controls were fostered to dams of the same line (in-fostered). Additional (population) control data were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…This extended vocalization response, and inability of these pups to reduce ultrasonic calls prior to weaning (day 21) possibly reflects a subtle developmental delay produced by REMSR. These results strongly suggest an early onset of anxiety behaviour in these pups which is supported by evidences from previously published work [30], [42]. Report of reduced USVs on postnatal day 9 in the vasopressin 1b knockout mice shows the vulnerability of ultrasonic vocalizations, and possibly social bonding, during early development [43].…”
Section: Discussionsupporting
confidence: 86%
“…This extended vocalization response, and inability of these pups to reduce ultrasonic calls prior to weaning (day 21) possibly reflects a subtle developmental delay produced by REMSR. These results strongly suggest an early onset of anxiety behaviour in these pups which is supported by evidences from previously published work [30], [42]. Report of reduced USVs on postnatal day 9 in the vasopressin 1b knockout mice shows the vulnerability of ultrasonic vocalizations, and possibly social bonding, during early development [43].…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the present findings are in line with studies of successful selective breeding for high or low calling rates in isolation (Brunelli 2005;Brunelli et al 1997Brunelli et al , 2001Brunelli et al , 2002Hofer et al 2001). Also, genetic analyses using reciprocal hybrids (Hahn et al 1987(Hahn et al , 1997(Hahn et al , 1998Hahn and Schanz 2002;Roubertoux et al 1996;Thornton et al 2005) revealed an influence of the genetic background on ultrasonic call emission; a finding, which is supported by studies on knockout mice.…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andsupporting
confidence: 78%
“…With respect to the rat study by Brunelli et al (2001) it has to be mentioned that they bred their animals for high or low calling rates by using a within-litter selection procedure which minimizes maternal effects . Despite this selection procedure, however, Rojowsky et al (2000) found that dams from the line with high calling rates showed reduced maternal responsiveness compared to dams from lines with random or low calling rates.…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andmentioning
confidence: 99%
“…Pups in the S13 generation were cross-fostered within 48 h of birth between dams of the two lines, that is, Low-pups to High-dams and High-pups to Low-dams (Brunelli, Hofer, & Weller, 2001). To control for fostering effects, other groups of pups were fostered to dams within their own lines (in-fostered).…”
Section: A Possible Role For Epigenetic Effectsmentioning
confidence: 99%